The Effect of Work-Life Balance and Work Engagement on Employee Performance with Job Satisfaction as a Mediating Variable: A Study of Semarang State Students Who Work Part-Time - Ratna Maulydia Saputri Hasibuan; Athoillah Athoillah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of work-life balance and work engagement on employee performance through job satisfaction as a mediating variable among Semarang State University students who work part time. The phenomenon of increasing student participation in part-time employment reflects the growing need for financial independence and work experience during higher education. However, balancing academic responsibilities and work demands often creates challenges that may influence job satisfaction and employee performance. This research applied a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The data were collected from 150 respondents consisting of Semarang State University students who worked part time. The results indicate that work-life balance has a positive and significant effect on job satisfaction and employee performance. Work engagement also positively and significantly influences job satisfaction and employee performance. Furthermore, job satisfaction positively influences employee performance and successfully mediates the relationship between work-life balance and employee performance, as well as work engagement and employee performance. These findings emphasize the importance of maintaining balance between work and personal life and strengthening employee engagement to improve performance among student workers.